2002
DOI: 10.1063/1.1445751
|View full text |Cite
|
Sign up to set email alerts
|

Simulating vapor–liquid nucleation of n-alkanes

Abstract: A combination of the aggregation-volume-bias Monte Carlo algorithm, the configurational-bias Monte Carlo algorithm, and the umbrella sampling technique was applied to investigate homogeneous vapor–liquid nucleation in ethane, n-butane, and n-heptane. The simple transferable potentials for phase equilibria-united atom (TraPPE-UA) force field was used in this investigation. It was found that for the n-heptane case, the TraPPE-UA force field predicted a nucleation rate that is about three to four orders of magnit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
99
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 68 publications
(109 citation statements)
references
References 57 publications
10
99
0
Order By: Relevance
“…However, neither chainlike molecules of n-nonane nor the orientationally dependent hydrogen-bonding interactions (involved by ethanol) can be modeled through the use of a spherical LJ bead. 39 Thus, it is difficult to draw connections between the systems examined by previous theoretical studies employing LJ models and the n-nonane/ethanol mixture studied here with atom-based force fields.…”
Section: Simulation Results and Discussionmentioning
confidence: 98%
“…However, neither chainlike molecules of n-nonane nor the orientationally dependent hydrogen-bonding interactions (involved by ethanol) can be modeled through the use of a spherical LJ bead. 39 Thus, it is difficult to draw connections between the systems examined by previous theoretical studies employing LJ models and the n-nonane/ethanol mixture studied here with atom-based force fields.…”
Section: Simulation Results and Discussionmentioning
confidence: 98%
“…For example, we repeated the phase equilibrium calculation reported for an nheptane system (with 300 molecules and a liquid box close to 40 Å) in Ref. 30 and found that more than 60% of the computer time was spent on the generation of the intramolecular angles. For an isolated molecule in a gas-phase, the angle generation consumed over 99% of the computer time.…”
Section: Background On Cbmcmentioning
confidence: 99%
“…A number of other studies have found that twobody molecular models fail to predict accurately and simultaneously the phase behavior and surface tension of real systems. 3,4,8,13,60 For example, the pure Lennard-Jones fluid, a potential commonly used in molecular modeling, reproduces the phase behavior of argon, but is unable to reproduce simultaneously and quantitatively its surface tension. 3,4,13,60 It is generally agreed upon that many-body effects need to be included in order to accurately reproduce the surface tension of argon.…”
Section: B Mixture IImentioning
confidence: 99%
“…The most straightforward approach is to simulate directly the interfacial region using molecular-dynamics or Monte Carlo simulation. [1][2][3][4][5][6][7][8][9][10] In this case, one simply juxtaposes the coexisting phases of interest and waits for an explicit interface to form and stabilize, which can require a significant amount of time. The interfacial tension is given by the mean difference between the normal and transverse components of the stress tensor calculated over the interfacial region.…”
Section: Introductionmentioning
confidence: 99%